Hubungan Antara Partisipasi Aktif dan Kemampuan Metakognitif Siswa Sekolah Dasar Melalui Metode Pembelajaran Montessori - Widia Nur Janah; Susilawati Susilawati (Jurnal Inovasi Pendidikan Dasar, 2019)
Metacognitive was the student’s skill in the process of acting (activity) and thinking (mental process). This skill could improve their learning process and memory. Student who had metacognitive skill will be able to control and to arrange his learning activity by himself. Active participation was the interaction both physically and psychologically to think, to interact, to try and to find new things in the learning process. The purpose of this research was to find the relationship between active participation and the metacognitive ability of students, especially in elementary school. This research was a correlation study. Population of this research was 5th grade students in SD Negeri 3 Klangenan academic year 2017/2018. Sample was taken using purposive sampling technique. The data was collected by observation and written test. The instruments for active participation was observation sheets and the instrument for metacognitive ability was a multiple choice test that consist of 20 questions. The data was analyzed using correlation technique using IBM SPSS Statistics 16.0 for windows. Based on the data nalaysis, it was obtained was 0.682. At a significant level 5% then was 0.413. Based on value then it showed that there was a positive and significant corelation between active participation and metacognitive ability of students 5th grade SD Negeri 3 Klangenan.